LEGAL EFFORTS TOWARDS WOMEN PROTECTION - Tayeng, Onyok; Akhtar, Ali; Sawar, Swati (International Journal of Psychosocial Rehabilitation, 2020)
People’s basic equal and inalienable rights as members of the global human community, regardless of gender, ethnicity, language, race, religion, nationality, or any other factor, can be summed up in the phrase "human rights." While India’s Constitution provides equality for both sexes, the actual state of women’s human rights in the country cannot be described as adequate despite these rights being recognised in the form of multiple fundamental rights. Due to the current structure and practices of Indian society, there is a significant discrepancy between the de facto and de jure conditions. As a result of India’s patriarchal system, the status of Indian women is lower than that of men. In every aspect of their lives, they are subject to prejudice, injustice, and shame because of their gender.